On-the-spot, easy and affordable soil testing for Kenyan smallholder farmers - Beek, Christy van; Coolen, Susanne; Leede, Berten de; Fiers, Teun; Helvoort, Angelique van (Technical Centre for Agricultural and Rural Cooperation, 2018)
Africa is facing an escalating soil fertility crisis and without immediate interventions, the continent continues to lose over 3,5 billion Euros per year worth of nutrients. To increase productivity whilst decreasing soil fertility decline, balanced fertilization is essential. Farmer cooperatives using soil scanners to provide real-time fertilizer recommendations to farmers may be part of the solution. AgroCares and Agriterra present their findings from a soil sensor services pilot for farmer cooperatives in Kenya.